The Effect of Family Room Lighting on Incidence of Positive AFB Lung TB in Serdang Bedagai Regency - Ika Dewi Purba; Rahayu Lubis; Nurmaini (Britain International of Exact Sciences (BIoEx) Journal, 2020)
The aims of the study is to find out the effect of lighting in family room. This type of research uses observational analytic studies with case-control study designs. The result of the study shows that there is the effect of lighting in the family room (p = 0.010, OR = 4.125, 95% CI = 1,473 - 11,555), lighting in the room (p = 0.009, OR = 3.167, 95% CI = 1,398-7,174) with the incidence of pulmonary TB, while the incidence of pulmonary TB disease, whereas occupancy density had no effect (p = 0.263). The result of multivariate analysis showed that lighting in the family room had the strongest influence with TB disease (p = 0.001 and Exp (B) of 24.560).